Plasma Glucose Concentrations in Different Sampling Tubes Measured on Different Glucose Analysers - Pleus, Stefan; Beil, Alexandra; Baumstark, Annette; Haug, Cornelia; Freckmann, Guido (Experimental and Clinical Endocrinology & Diabetes, 2024)
Introduction The German Diabetes Association recommends using sampling tubes with citrate and fluoride additives to diagnose diabetes by oral glucose tolerance test to inhibit glycolysis. The effect of different tubes on measurement results was assessed.Materials and Methods In a first study, an oral glucose tolerance test was performed on 41 participants without anamnestically known diabetes. Venous blood was sampled in two different tubes with citrate/fluoride additives from different manufacturers and one with only lithium-heparin additive. A second study with 42 participants was performed to verify the initial results with an adapted design, in which a third tube with citrate buffer was used, and glucose measurements were performed on two additional devices of another analyser model. Samples were centrifuged either immediately (<5 min incubation time) or after 20 min or 4 h. All glucose measurements were performed in plasma. Glucose concentrations in lithium-heparin tubes with<5 min incubation time served as baseline concentrations.Results In the first study, glucose concentrations in one of the citrate/fluoride tubes were similar to the baseline. In the other citrate/fluoride tube, markedly lower concentrations (approximately − 5 mg/dL (− 0.28 mmol/L)) were measured. This was reproduced in the verification study for the same analyser, but not with the other analyser model. Lithium-heparin tubes centrifuged after 20 and 240 min showed systematically lower glucose concentrations.Conclusions The results confirm that glycolysis can be effectively inhibited in citrate/fluoride-containing sampling tubes. However, glucose measurement results of one analyser showed a relevant negative bias in tubes containing liquid citrate buffer.
Keywords: oral glucose tolerance test; glycolysis inhibition; diabetes diagnosis; interference